Evaluasi Produk Gendongan Bayi Menggunakan Metode Kansei Engineering - Anandari Ramadhiar Priyandini; Ari Widyanti (The Industrial Engineering Department of Engineering Faculty at Universitas Andalas, 2020)
There are a lot of baby carrier types commonly found in Indonesia. Aside from the massively produced baby carriers with modern shapes and features, the traditional ‘kain jarik’ baby carriers are still an option to mothers in Indonesia. The research was conducted to evaluate the subjective perception of the consumers in choosing to use a baby carrier. An evaluation was done to see the factors that influence consumers to choose a certain product and their correlations to the products’ designs. Kansei engineering is used as a method to identify the emotional perception of a consumer to a baby carrier by means of a questionnaire involving 525 respondents. The identification process results in several Kansei words that were grouped and used as a stimulus to the questionnaires meant to evaluate 4 samples of baby carriers commonly used in Indonesia. The result showed that there are 3 main factors that encouraged consumers to pick a baby carrier, which are comfort, design, and material. Based on those 3 factors, consumers gave their highest scores to a kangaroo or wrap baby carriers.